Pengaruh Pemberian Pupuk Bokashi Feses Sapi Sumba Ongole Terhadap Nilai Nutrisi Legum Indigofera Zollingeriana - Arlando Pila Ndilu; Marselinus Hambakodu (Universitas Kristen Wira Wacana Sumba, 2023)
This study aims to determine the effect of bokashi fertilizer on the feces of Sumba Ongole cattle on the nutritional value of the Indigofera Zollingeriana legume. This study used a completely randomized design (CRD) with 5 treatments and 4 replications namely; P0: without the application of bokashi manure of Sumba Ongole cattle, P1: bokashi fertilizer of 200 grams/planting hole, P2: bokashi fertilizer of 500 grams/planting hole of Sumbanese Ongole cattle feces, P2: 800 gram/planting hole of Sumbanese Ongole cattle faeces bokashi fertilizer planting hole, P4: 1000 grams of bokashi fertilizer from the faeces of Sumba Ongole cattle/planting hole. The variables measured were crude protein and crude fiber. The results showed that the treatment had a significant effect (P<0.05) on crude protein and crude fiber. The conclusion of the application of bokashi fertilizer on the faeces of Sumba Ongole cattle at a level of 200 g/planting hole produces crude protein content and the higher the level of fertilizer application, the lower the crude fiber content.